Reactive oxygen species scavenging enzyme activities in berangan banana plant infected by Fusarium oxysporum f. sp. cubense - Fung, Shi Ming; Razali, Zuliana; Somasundram, Chandran (Faculty of Science, Chiang Mai University, 2019)
Fusarium oxysporum f. sp. cubense (FOC), a hemibiotrophic soil-borne pathogen is responsible for the most dreadful disease for banana plants worldwide. It is crucial to study the defense mechanism of banana plants against this disease in order to facilitate studies on future solutions. Increasing levels of reactive oxygen species (ROS) such as superoxide anions (O·2), hydrogen peroxide (H2O2), hydroxyl radicals (•OH) were among the earliest responses observed in banana plants following invasion by the offending pathogen and play an essential role in plant defense system. In order to have a more complete view of the berangan banana plant enzymatic antioxidant system, superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), peroxidase (POD), ascorbate peroxidase (APX), and glutathione reductase (GR) were analyzed in different parts of the plants: Roots, pseudostems and leaves. We observed a biphasic change in the ROS level and enzymatic activities in the infected plants. The ROS increased throughout the infection period while enzyme activities increased at the early stages of infection then decreased at later stages. The decline in the enzyme activities and the continuous increment in ROS at the later stages allow FOC to grow, thus increasing infection and eventually leading to necrosis. This suggests that these enzymes play an important role in berangan plant defense against FOC infection. © 2019, Chiang Mai University. All right reserved.